Analysis of the Use of Rational Electric Vehicle Battery Design as an Example of the Introduction of the Fit for 55 Package in the Real Estate Market - Oleksandr Beshta; Dariusz Cichoń; Oleksandr Beshta; Taras Khalaimov; Edgar Cáceres Cabana (Energies, 2023)
The European climate law contains a mandatory EU climate target of reducing emissions in the EU by at least 55% by 2030; to realistically implement it, a transformation of many economic sectors is required. The main solutions focus on energy production. However, an equally important aspect is its storage. It represents the biggest challenge to ensure the stability of energy use in the real estate market. Today, lithium-ion batteries are the most promising batteries. They have the advantages of high efficiency during the charge–discharge process, and high density of electrical energy. The potential range of electric vehicles on a single charge depends on the battery. Accumulator batteries, depending on their purpose, are assembled from a certain number of lithium-ion cells. At the same time, the battery connection scheme depends on what the goal is. This can be an increase in battery capacity, an increase in voltage, or a combination of both parametric characteristics of the device. This approach and research results can be implemented not only in the automotive field, but also in industry, the real estate market, etc.